Etnobotani Tumbuhan Obat Tradisional yang Dimanfaatkan Suku Dayak Ngaju di Kelurahan Tewah Kabupaten Gunung Mas - Sintia , Vinni; Sunariyati, Siti; Krestina, Widya (Universitas Bengkulu, 2025)
The Ngaju Dayak tribe in Tewah Village still uses plants as medicine to cure various diseases. This study aims to identify the species and parts of medicinal plants used by the Dayak Ngaju tribe in Tewah Village, as well as the processing methods and use values of these plants. This descriptive study uses qualitative and quantitative approaches (mixed methods research) and was conducted in Tewah Village. The stages of the research process consist of field observations and the selection of informants to be interviewed, with the latter being determined by the established criteria. The interview was conducted using a semi-structured interview technique, in which plant samples were obtained with the assistance of informants. The plant samples found are then documented, described, identified, and added to a herbarium collection. The result of the research obtained 44 species of medicinal plants that have been utilized for medicinal purposes by the Ngaju Dayak Tribe. The various components of plants that are utilized for medicinal purposes include roots, stems, leaves, fruits, branches, twigs, and sap. The processing of the plants utilized in this method encompasses a variety of techniques, including boiling, heating, pounding, squeezing, baking, and soaking. There are 2 species of medicinal plants, namely plants kayu sambung maut (Condiaeum variegatum) and kangkawang kapas (Leea indica), that have a Use Value (UV) higher than the other 42 plant species. The Relative Use Value (RUV) of the 4 plant species that were predominantly utilized was 4.19.